Current Account Determinants for Oil-Exporting Countries - Morsy, Hanan (IMF Working Papers; Working Paper, 2009)
The paper aims at characterizing the main determinants of the medium-term current account balance for oil-exporting countries using dynamic panel estimation techniques. Previous studies included a very limited number of oil-exporting countries in their samples, raising concerns about the applicability of the estimated coefficients for oil countries. Furthermore, current approaches are not specifically tailored to oil-producing countries because they fail to capture the effects of oil wealth and the degree of maturity in oil production. This paper explores the underlying determinants of the current account balance for a large sample of oilexporting countries, and extends the specifications commonly used in the literature to include an oil wealth variable, as well as a proxy for the degree of maturity in oil production. The paper therefore contributes to the existing literature both in terms of the sample studied as well as the variables considered. The results reveal that factors that matter in determining the equilibrium current account balance of oil-exporting counties are the fiscal balance, the oil balance, oil wealth, age dependency, and the degree of maturity in oil production.